Part-time jobs: what women want? - Alison L. Booth; Jan C. van Ours (Institute for the Study of Labor (IZA), 2010)
Part-time jobs are popular among partnered women in many countries. In the Netherlands the majority of partnered working women have a part-time job. Our paper investigates, from a supply-side perspective, if the current situation of abundant part-time work in the Netherlands is likely to be a transitional phase that will culminate in many women working full-time. We analyze the relationship between part-time work and life satisfaction, and between job satisfaction and preferred working hours using panel data on life and job satisfaction for a sample of partnered women and men. We also utilize time-use data to consider the distribution within the household of market work and housework, and discuss the work specialization hypothesis in this context. Our main results indicate that partnered women in part-time work have high levels of job satisfaction, a low desire to change their working hours, and live in partnerships in which household production is highly gendered. Taken together, our results suggest that part-time jobs are what most Dutch women want.
Keywords: J22; I31; J16; 330; Part-time work; happiness; satisfaction; working hours; gender; Teilzeitarbeit; Frauenerwerbstätigkeit; Arbeitszeit; Leistungsmotivation; Lebenszufriedenheit; Geschlecht; Niederlande